Outcome of Aneurysmal Subarachnoid Haemorrhage at Posterior Communicating Artery with Obstructive Hydrocephalus Post Successful Surgical Clipping and External Ventricular Drainage: A Case Report - Dyah Fiharjatin; Tommy Rachmat Setyawan; Rakhian Listyawan; Fajar Maskuri (Magna Neurologica, 2026)
Background: Approximately 25% of patients with SAH die before hospital admission. Proper posterior communicating artery (PCoA) aneurysm-related SAH is rare, with an incidence of about 1%. It is typically treated with coil embolization via digital subtraction angiography (DSA). In this case, decompressive craniectomy and external ventricular drainage (EVD) were performed, followed by aneurysm clipping, resulting in an excellent outcome. Case: A 63-year-old woman presented with a sudden severe headache, vomiting, somnolence, and right-sided limb weakness. Head CT angiography revealed SAH from a ruptured saccular aneurysm with a daughter aneurysm on the PcoA, Modified Fisher scale 2, and intraventricular hemorrhage (IVH) with a modified Graeb score of 3. The patient underwent decompressive craniectomy, EVD placement, and aneurysm clipping. On postoperative day two, she was alert but had left oculomotor nerve palsy and global aphasia. Head CT showed an acute infarction. Nicardipine was administered for a hypertensive emergency. Intravenous ceftazidime and gentamicin were used to treat nosocomial pneumonia. Nutritional support, physiotherapy, and speech therapy were provided. Discussion: Clipping was chosen for higher aneurysm obliteration rates and better oculomotor nerve recovery, despite a higher risk of postoperative cerebral ischemia than coiling. Due to high Modified Fisher and Graeb scores, EVD was necessary. Hemodynamic management and pneumonia treatment were critical. Early intervention, multidisciplinary care, and close postoperative monitoring are essential to reduce mortality and improve outcomes in PcoA aneurysm-related SAH. Conclusion: Decompressive craniectomy, EVD, and clipping combined with optimal hemodynamic management and complication control resulted in satisfactory outcomes in this rare PcoA aneurysm SAH case.